2019
DOI: 10.1093/icvts/ivz159
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridization for identification and visualization of microorganisms in infected heart valve tissue as addition to standard diagnostic tests improves diagnosis of endocarditis

Abstract: OBJECTIVES In infective endocarditis (IE), identification of the causative organism and consecutive treatment are crucial for patient survival. Although the macroscopic aspect resembles infected tissue, standard diagnostic tests often fail to allow one to identify bacteria. Fluorescence in situ hybridization (FISH) is a molecular, culture-independent technique that allows one to identify and visualize microorganisms within tissue and to recognize their morphology, number and activity. We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…FISHseq identified PVE-causing pathogens in approximately one-third of the cases with noninformative (negative, inconclusive, or missing) BCs. In addition, in the study of Eichinger et al [ 39 ], FISHseq turned out to be the most effective diagnostic test for pathogen detection in native valve endocarditis. In this study, FISHseq identified microorganisms in 103 of 128 (80.4%) cases, whereas BCs were positive in 67 of 128 (52.3%) cases and VCs only in 34 of 128 (34%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…FISHseq identified PVE-causing pathogens in approximately one-third of the cases with noninformative (negative, inconclusive, or missing) BCs. In addition, in the study of Eichinger et al [ 39 ], FISHseq turned out to be the most effective diagnostic test for pathogen detection in native valve endocarditis. In this study, FISHseq identified microorganisms in 103 of 128 (80.4%) cases, whereas BCs were positive in 67 of 128 (52.3%) cases and VCs only in 34 of 128 (34%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) in combination with 16S RNA-directed PCR and sequencing (FISHseq) is a molecular method that has proven useful for the detection and identification of bacteria in clinical samples, in particular in biofilm-associated diseases and culture-negative infections. 22 , 23 As a microscopic technique, FISH visualizes an infection landscape of the tissue sample showing where specific microbial species are found, and in which state they are. This is important because resistant bacteria may persist in the deep tissue of the sternal wound.…”
Section: Discussionmentioning
confidence: 99%
“…Multilocus sequence typing was performed via the PubMLST webtool, which revealed that this strain (denominated as IMT 49926) belongs to the ST35 type (Table 3). Fluorescence in situ hybridization (FISH) of the heart valve tissue sections was performed to visualize the microbial biofilms in situ as described before [2,3]. The heart valve sample was briefly fixated, embedded in cold polymerizing resin, and sectioned.…”
Section: Case Presentationmentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) of the heart valve tissue sections was performed to visualize the microbial biofilms in situ as described before [ 2 , 3 ]. The heart valve sample was briefly fixated, embedded in cold polymerizing resin, and sectioned.…”
Section: Case Presentationmentioning
confidence: 99%